Fuzzy soft k−ideals over semiring and fuzzy soft semiring homomorphism - Marapureddy Murali Krishna Rao; B. Venkateswarlu (Journal of Hyperstructures)
In this paper, we introduce the notion of fuzzy soft semirings, fuzzy soft ideals, fuzzy soft k− ideals , k−fuzzy soft ideals over semirings and fuzzy soft semiring homomorphism. We study some of their algebraical properties and properties of homomorphic image of fuzzy soft semiring.